Heart rate variability and implication for sport concussion. (16th November 2017) - Bishop, Scott A.; Dech, Ryan T.; Guzik, Przemyslaw; Neary, J. Patrick
Summary: Finding sensitive and specific markers for sports‐related concussion is both challenging and clinically important. Such biomarkers might be helpful in the management of patients with concussion (i.e. diagnosis, monitoring and risk prediction). Among many parameters, blood flow–pressure metrics and heart rate variability (HRV) have been used to gauge concussion outcomes. Reports on the relation between HRV and both acute and prolonged concussion recovery are conflicting. While some authors report on differences in the low‐frequency (LF) component of HRV during postural manipulations and postexercise conditions, others observe no significant differences in various HRV measures. Despite the early success of using the HRV LF for concussion recovery, the interpretation of the LF is debated. Recent research suggests the LF power is a net effect of several intrinsic modulatory factors from both sympathetic and parasympathetic branches of the autonomic nervous system, vagally mediated baroreflex and even some respiratory influences at lower respiratory rate. There are only a few well‐controlled concussion studies that specifically examine the contribution of the autonomic nervous system branches with HRV for concussion management. This study reviews the most recent HRV– concussion literature and the underlying HRV physiology. It also highlights cerebral blood flow studies related to concussion and the importance of multimodal assessment of various biological signals. It is hoped that a better understanding of the physiology behind HRV might generate cost‐effective, repeatable and reliable protocols, all of which will improve the interpretation of HRV throughout concussion recovery.